Ichthyosis uteri complicated by poorly differentiated endometrial adenocarcinoma with squamous differentiation - Shi, Haiyan; Chen, Xiaoduan; Zhang, Suojiang; Zhou, Caiyun (Menopause Review/Przegląd Menopauzalny, 2013)
Endometrial squamous metaplasia is a common type of metaplasia. Wide endometrial squamous metaplasia, or ichthyosis uteri, is a rare form of the disease. Malignant transformation based on ichthyosis uteri alone or ichthyosis uteri complicated by other malignant lesions is even rarer. In this study, we report a case of ichthyosis uteri complicated by poorly differentiated endometrial adenocarcinoma. A 74-year-old patient visited the doctor’s office after suffering from irregular and small amounts of vaginal hemorrhage for half a month. Gynecological examination showed a 2-month pregnancy-like uterine enlargement. Histopathological examination confirmed two types of lesions: poorly differentiated endometrioid adenocarcinoma and wide replacement of a large area of endometrium by mature squamous epithelium. Based on previous studies and the current report, the malignant potential of ichthyosis uteri or its simultaneous occurrence with other malignant lesions cannot be completely excluded, although the lesion observed was only considered a benign lesion.